Metal industry in civilizations old world (Journal of the College of Basic Education, 2022)
The metal industry is one of the features of building, developing, and advancing civilization, and its uses had a great and wide impact on the development of the daily lives of the peoples of the ancient world, and thus the advancement of those societies and the building of civilization. Mining and metallurgy processes contributed to showing the bright face of every civilization of the ancient world. I have studied many areas of creativity and innovation for the various components of civilization and urbanization, but our study is a detailed study of the discovery and manufacture of minerals in the ancient civilizations of the world.